Shifts and Turns in Families in Distressful Phenomenon: Reflections on the COVID-19 Pandemic in South Africa - Kajiita, Robert Mutemi (Journal of Ecohumanism, 2025)
The COVID-19 pandemic profoundly disrupted family life in South Africa, reshaping roles, relationships, and cultural practices. This paper explores the “shifts and turns” families undertook to navigate lockdowns, economic hardship, and health anxieties. Drawing on qualitative document analysis and Walsh’s Family Resilience Framework, the study highlights dual outcomes of the crisis: intensified vulnerabilities—such as strained parent-child dynamics, disrupted partner intimacy, increased domestic violence, and the disproportionate caregiving burden on women—alongside adaptive strategies that fostered resilience, cooperation, and reconnection. Families turned to digital technologies, shared responsibilities, and new rituals to sustain cohesion, while cultural losses around caregiving, mourning, and communal life revealed deep psychosocial costs. The findings demonstrate that resilience was unevenly distributed, often mediated by pre-existing inequalities, yet the pandemic also opened opportunities to challenge entrenched gender roles and reimagine family support systems. The paper concludes with recommendations for post-pandemic recovery policies that strengthen social welfare, address gender-based violence, and support culturally sensitive mental health interventions to reinforce family resilience during future crises.